2018
DOI: 10.1159/000479239
|View full text |Cite
|
Sign up to set email alerts
|

RHD-Positive Alleles among D- C/E+ Individuals from India

Abstract: Background: Molecular bases of blood group systems, including Rh blood group, have been poorly studied in the Indian population so far, while specificities of Europeans, East Asians and Africans have been well known for years. In order to gain insights into the molecular bases of this population, we sought to characterize the RHD allele in D- Indian donors expressing C and/or E antigen(s). Methods:RHD gene was analyzed in 171 serologically D-, C/E+ samples by standard molecular methods such as quantitative, mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…As expected, whole RHD gene deletion at the homozygous state is the most common D-negative genotype in serological D-negative Thai blood donors (Table 1, 75.0%). When considering only the subset of C/E+ samples (n = 100), frequency of this genotype is in the range of what has been reported before in other Asian populations (36.4-63.1%) [15,16,25,26]. Interestingly, as many as 21 samples out of 200 were found to carry the Asian DEL allele.…”
Section: Discussionsupporting
confidence: 52%
“…As expected, whole RHD gene deletion at the homozygous state is the most common D-negative genotype in serological D-negative Thai blood donors (Table 1, 75.0%). When considering only the subset of C/E+ samples (n = 100), frequency of this genotype is in the range of what has been reported before in other Asian populations (36.4-63.1%) [15,16,25,26]. Interestingly, as many as 21 samples out of 200 were found to carry the Asian DEL allele.…”
Section: Discussionsupporting
confidence: 52%
“…There is limited data 12 13 on serological prevalence of D variants (partial D/weak D) using commercially available RhD phenotyping panels and few studies on molecular characterization of suspected partial D samples 14 15 . Kulkarni et al 16 have identified hybrid genes in 59/171 (31%) of select (C/E+) subgroup of serological RhD-negative individuals from India. The present study was undertaken to find out prevalence of apparently RhD-negative individuals which may be identified on molecular testing as RhD-positive.…”
mentioning
confidence: 99%
“…We have observed that when the molecular report does not provide an interpretation and recommendation, clinical practictioners not experienced in blood group genetics hesitate to interpret RHD genotyping results as D+ or D−. For the purposes of RhIG adminstration and transfusion, interpretation of an RHD genotype requires not only pertinent experience but also knowledge of the history 2,5 as well as the current evolving data [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] and literature reports 15,16,[23][24][25][26] of the risks for alloimmunization associated with specific RHD genotypes. 27 Hospital computer systems may require updating to accomodate new requirements, such as the ability to change a prior serologic D typing result, when it is overridden by a different D type based on RHD genotyping results.…”
mentioning
confidence: 99%